A new mode of NPR1 action via an NB‐ARC–NPR1 fusion protein negatively regulates the defence response in wheat to stem rust pathogen. Issue 3 (26th August 2020) - Wang, Xiaojing; Zhang, Hongtao; Nyamesorto, Bernard; Luo, Yi; Mu, Xiaoqian; Wang, Fangyan; Kang, Zhensheng; Lagudah, Evans; Huang, Li
Summary: NPR1 has been found to be a key transcriptional regulator in some plant defence responses. There are nine NPR1 homologues ( TaNPR1 ) in wheat, but little research has been done to understand the function of those NPR1 ‐like genes in the wheat defence response against stem rust ( Puccinia graminis f. sp. tritici ) pathogens. We used bioinformatics and reverse genetics approaches to study the expression and function of each TaNPR1 . We found six members of TaNPR1 located on homoeologous group 3 chromosomes (designated as TaG3NPR1 ) and three on homoeologous group 7 chromosomes (designated as TaG7NPR1 ). The group 3 NPR1 proteins regulate transcription of SA‐responsive PR genes. Downregulation of all the TaNPR1 homologues via virus‐induced gene co‐silencing resulted in enhanced resistance to stem rust. More specifically downregulating TaG7NPR1 homeologues or Ta7ANPR1 expression resulted in stem rust resistance phenotype. By contrast, knocking down TaG3NPR1 alone did not show visible phenotypic changes in response to the rust pathogen. Knocking out Ta7ANPR1 enhanced resistance to stem rust. The Ta7ANPR1 locus is alternatively spliced under pathogen inoculated conditions. We discovered a new mode of NPR1 action in wheat at the Ta7ANPR1 locus through an NB‐ARC–NPR1 fusion protein negatively regulating the defence to stem rust infection.